Factors Affecting Radial Artery Occlusion After Right Transradial Artery Catheterization for Coronary Intervention and Procedures - Xu D; Liu Y; Xu C; Liu X; Chen Y; Feng C; Lyu N (Dove Medical Press, 2023)
Dujuan Xu,1,* Ying Liu,1,* Chao Xu,2,* Xuekui Liu,3 Ye Chen,1 Chunguang Feng,4 Nan Lyu1 1Department of Ultrasound, Xuzhou Central Hospital, Xuzhou, People's Republic of China; 2Department of Radiology, Xuzhou Children's Hospital, Xuzhou, People's Republic of China; 3Department of Central Laboratory, Xuzhou Central Hospital, Xuzhou, People's Republic of China; 4Department of Cardiology, Xuzhou Central Hospital, Xuzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Nan Lyu; Chunguang Feng, Email kksfm8833@qq.com; fcg999@163.comObjective: To determine the factors influencing proximal radial artery occlusion (PRAO) right radial artery after coronary intervention.Methods: This is a single-center prospective observational study. A total of 460 patients were selected to undergo coronary angiography (CAG) or percutaneous coronary intervention (PCI) via the proximal transradial approach (PTRA) or distal transradial approach (DTRA). The 6F sheath tube were received by all patients. Radial artery ultrasound was performed 1 day before procedure and 1- 4 days after procedure. Patients were divided into the PRAO group (42 cases) and the non-PRAO group (418 cases). General clinical data and preoperative radial artery ultrasound indexes of the two groups were compared to analyze related factors leading to PRAO.Results: The total incidence of PRAO was 9.1%, including 3.8% for DTAR and 12.7% for PTRA. The PRAO rate of DTRA was significantly lower than that of PTRA (p < 0.05). Female, low body weight, low body mass index (BMI) and CAG patients were more likely to develop PRAO after procedure (p < 0.05). The internal diameter and cross-sectional area of the distal radial artery and proximal radial artery were smaller in the PRAO group than in the non-PRAO group, and the differences were statistically significant (p < 0.05). Multifactorial model analysis showed that the puncture approach, radial artery diameter and procedure type were predictive factors of PRAO, and the receiver operating characteristic curve showed a good predictive value.Conclusion: A larger radial artery diameter and DTRA may reduce the incidence of PRAO. Preoperative radial artery ultrasound can guide the clinical selection of appropriate arterial sheath and puncture approach.Keywords: proximal radial artery occlusion, coronary intervention, ultrasound, influencing factors, the distal transradial approach